Evidence that traffic noise increases territorial response in vermilion flycatchers - Chavez-Mendoza, Nayeli Evelin; José-Ramírez, Sandra; Ríos-Chelén, Alejandro Ariel (Frontiers in Ecology and Evolution, 2023)
Animals vocalize in particular ways in noise, presumably to increase the probability of detection; however, this idea has been seldom put to the test. Vermilion flycatchers produce longer songs in noisy territories. To test the hypothesis that longer songs increase the probability of detection in noise, we ran a field playback experiment on 30 free-living males. Each male was exposed to two treatments with the same songs, but one treatment had traffic noise and the other had no noise. Half of males were exposed to short songs (with four introductory elements-IE) and half to long songs (eight IE). If long songs have a higher probability of detection in noise, we expected that the experimental noise would have little effect when males heard long songs, but a larger effect when they heard short songs (i.e. significant interaction between song length and treatment). We measured call and flight responses, latencies to call and fly, and closest approach to the speaker. We also measured ambient traffic noise in the males’ territories to evaluate a possible association with their responses. Males did not respond differently to long vs short songs; more importantly, the predicted interaction between song length and treatment was not found. Our results, do not support the hypothesis that long songs are detected with a higher probability in noise. Interestingly, males increased their call response as ambient noise increased in their territories. Males also showed a non-significant trend to increase their flight respond toward long songs with experimental noise than to long songs without noise. Our results strongly suggests that noise amplifies territorial response, which may affect the outcome of territorial competition.